Outcome of External Dacryocystorhinostomy Operation with and without Posterior Nasal Mucosal Flap Suturing Technique in Combined Military Hospitals of Bangladesh - Akhter, Amina (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: External Dacryocystorhinostomy is an anastomosing operation which creates a fistula between the medial wall of lacrimal sac and lateral wall of nasal cavity. Objectives: To compare the success rate by suturing both the anterior and posterior nasal mucosal flaps and without suturing the posterior nasal mucosal flap in External DCR surgery of 50 cases in different Combined Military Hospitals (CMH) of Bangladesh. Methods: The study included 50 cases of Chronic Dacryocystitis patients with symptoms of epiphora and blocked Sac Patency Test (SPT). External Dacryocysto- rhinostomy (DCR) surgery was done by same surgeon in different CMH over the period of 02 years extending from January 2016 to December 2017. Total 50 patients were divided into equal 02 groups. Group A underwent External DCR with silicone tube intubation and both anterior and posterior nasal mucosal flaps were sutured. Group B underwent similar DCR surgery where only anterior nasal mucosal flaps were sutured with lacrimal sac flap and posterior mucosal flap was excised completely. Results: External DCR surgery success rate was evaluated by a patent SPT at 03 months, 06 months and 12 months post operatively in both groups. SPT was successful in 92% cases in group A and 96% in group B at 3 months follow up after silicone tube removal. At 6 months reduction of epiphora occurred in 90% cases in Group A and 96% cases in Group B with unchanged SPT percentage. At 12 months follow up result remained unchanged as found at 6 months. There was significant difference in success rate of two different surgical technique. Quality of surgery improved with less intraoperative complications with shorter surgical time when only anterior nasal mucosal flap was sutured with excision of posterior nasal flap. Conclusion: This study suggested that comparing both the techniques of with and without suturing anterior and posterior nasal mucosal flaps in external DCR surgery, the later one makes considerable improvement in success rate of DCR. Excising the posterior nasal mucosal flaps can reduce operation time, improve operation technique and reduced epiphora post surgically. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 31-33